PWE-077 Pilot of flexible sigmoidoscopy screening to prevent colorectal cancer. (28th May 2012) - Sofianopoulou, E; Rubin, G; Ritchie, M; Patnick, J; Rees, C
Abstract : Introduction: A screening programme in England to prevent colorectal cancer using flexible sigmoidoscopy (FSIG) was announced in late 2010, following the results of a major UK study showing that a one-off FSIG offered to people aged 55–64 years significantly reduced colorectal cancer incidence and mortality. Three "pathfinder" sites, in Derby, South of Tyne and Tees, were selected to assess the practicalities of invitation and FSIG screening. We report the findings of our evaluation of this pathfinder phase. Methods: Patients aged 55 yrs and registered with one of 31 selected practices in three pathfinder areas received postal invitations to participate. The South of Tyne and Derby sites employed similar, interactive model of screening invitation involving telephone pre-assessment by specialist screening practitioners, while Tees used a simple invitation. We used routinely collected data to assess screening uptake, process and outcomes. A self-completion patient satisfaction questionnaire was sent 1-month after attendance to all participants. A postal questionnaire was sent to the 31 participating GP practices that had been selected to participate. Screening took place for a 3-month period in early 2011. Results: In total 4022 people aged 55 years were invited and 1129 (28%) screened over the 3-month period. Screening uptake differed by method of invitation, with a simple approach being significantly more successful than one that was more interactive (32% vs 27%, p=0.0015). Uptake also decreased significantly with increasing deprivation. Adenomas were found in 111 (9.8%) of those screened. Cancer was found in two subjects. Over 95% of participants rated the procedure as "very" or "fairly" acceptable. Over 90% of respondents said they would participate in cancer screening in the future and a similar proportion would recommend doing so to others. 11 out of 31 practices offered an estimate of the time spent on activities relating to this pathfinder for FSIG screening, most giving a figure of <1%. Conclusion: In this pathfinder study, a simple invitation to FSIG achieved a greater uptake rate than a more complex, interactive method of invitation. Deprivation was associated with lower screening uptake. Further pilots of the flexible sigmoidoscopy screening programme should focus on strategies to increase response rate and to improve technical aspects of the procedure. Further evaluation should be incorporated into that development. Competing interests: None declared.